The performance of perennial ryegrass in binary mixtures with lucerne and red clover under n fertilization - Bijelić Zorica; Mandić Violeta; Krnjaja Vesna; Ružić-Muslić Dragana; Simić Aleksandar; Cekić Bogdan; Caro-Petrović Violeta (Biotechnology in Animal Husbandry, 2017)
Perennial ryegrass is a very important and widespread grass species used for livestock nutrition, in particularly ruminants. As a species that is most commonly used on grasslands, it is grown in mixtures with other types of grasses and legumes. The objective of the research was to investigate the performance of perennial ryegrass at various proportions in the mixtures with red clover and lucerne, and how different levels of N fertilization affect its competitiveness. Ryegrass achieved the highest yield with lucerne at seeding rate 50:50 and with red clover at seeding rate 70:30. Relative grass yield (RYg) of mixtures ranged from 1.01 to 1.55 respectively, which means that ryegrass in mixtures achieved 0.1-55% greater yield than pure ryegrass crop. N fertilization increased DMY and RYg, leaf : steam ratio, specific leaf area (SLA), leaf area ratio (LAR) and leaf area index (LAI) in both years thus increasing the competitive capability of perennial ryegrass.